Exploration on the corrosion inhibition performance of Salvia miltiorrhiza extract as a green corrosion inhibitor for Q235 steel in HCl environment - Cheng Zeng; Zong-Yi Zhou; Wen-Jie Mai; Qiu-Hao Chen; Jin-Bei He; Bo-Kai Liao (Journal of Materials Research and Technology, 2024)
Salvia Miltiorrhiza, extensively distributed and commonly employed as a traditional Chinese medicinal herb, has garnered significant attention. In this study, the Salvia Miltiorrhiza extract (SME) was prepared by one-step water extraction method, and was firstly used as a novel corrosion inhibitor for Q235 steel in 1 mol/L HCl solution. As identified via liquid chromatography-mass spectrometry, the findings reveal that Salvianic acid A, tanshinone II A, danshenxinkun D, dihydrotanshinone, and methylene tanshinquinone are the primary constituents of SME. The optimum corrosion inhibition efficiency reached 92.8 % at 200 mg/L and maintained at 90.4 % after 72 h. Based on in-situ scanning vibration electrode technology (SVET) monitoring, the adsorption of inhibitor molecules on metal surface greatly retarded the propagation of localized corrosion. AFM examination of the corroded surface reveals that the samples supplemented with SME exhibit a smoother surface compared to the blank group. The force curve graph for the SME-added group demonstrates a more evenly distributed point array and an elevated average adhesion force, indicating that the addition of SME improves the corrosion resistance of the metal surface. XPS characterization illustrated that SME interacted with iron ions to form insoluble precipitate. This work investigated the application of SME as an eco-friendly corrosion inhibitor for carbon steel in acidic medium, providing a new approach for the high value-added utilization of Salvia Milliorrhiza.